2017
DOI: 10.1155/2017/9407675
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Limited Granulomatosis with Polyangiitis Involving Vagina and Urethra

Abstract: Granulomatosis with polyangiitis (GPA) is a systemic necrotizing granulomatosis vasculitis characterized by predilection to affect small- and medium-sized blood vessels and commonly affects the upper and lower respiratory tract and kidneys in most cases. Genital involvement is reported in <1% of cases in large cohorts and nearly all cases have been in the setting of multisystemic disease or during the course of the disease in patients already diagnosed as GPA. A case is presented of uncommon limited urogenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A higher recurrence rate is observed with a diagnosis delay of 12 months or longer. However, there is not a single patient with genital involvement and without a uterus (previous hysterectomy or performed at diagnosis) who has experienced a recurrence, including our patient [14,15,18,19].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…A higher recurrence rate is observed with a diagnosis delay of 12 months or longer. However, there is not a single patient with genital involvement and without a uterus (previous hysterectomy or performed at diagnosis) who has experienced a recurrence, including our patient [14,15,18,19].…”
Section: Discussionmentioning
confidence: 91%
“…Our systematic review identified 19 patients with GPA and genital tract involvement [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Among them 11/19 (58%) had primary disease, and 8/19 (42%) had recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations